2003
DOI: 10.1007/s00221-003-1551-0
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of the bilateral distribution advantage

Abstract: Letters can be matched by their physical identity (i.e., a-a: same/A-a: different) or by their name (both a-a and A-a: same). The latter, more demanding task has in previous experiments led to an advantage of bilateral over within-hemifield matches, which was not observed in the former. We have investigated the neural basis of this bilateral distribution advantage (BDA) in letter name matching with event-related fMRI. Unilateral, compared to bilateral, name matching led to increased activation in the contralat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…A functional imaging study using a variation of the Banich paradigm demonstrated that a more complex letter name task led to more bilateral activation in the fusiform and lateral occipital gyri than a less complex letter shape task (Pollmann, Zaidel, & Cramon, 2003). These findings are consistent with the view that interhemispheric resource sharing increases with increasing task demands.…”
Section: Introductionsupporting
confidence: 61%
“…A functional imaging study using a variation of the Banich paradigm demonstrated that a more complex letter name task led to more bilateral activation in the fusiform and lateral occipital gyri than a less complex letter shape task (Pollmann, Zaidel, & Cramon, 2003). These findings are consistent with the view that interhemispheric resource sharing increases with increasing task demands.…”
Section: Introductionsupporting
confidence: 61%
“…A and a) than physical matches (e.g. A and A) (Pollman et al, 2003), greater bilateral activation was found to negative than positive stimuli, whether the stimuli were faces with negative expressions (Killgore & Yurgelun-Todd, 2007) or were unpleasant images (Gerdes et al, 2010). Taken together, the evidence is compelling to suggest that the processing of negative stimuli is more demanding than positive stimuli.…”
Section: Introductionmentioning
confidence: 76%
“…Hemispheric interaction is predicted to benefit the processing of negative images, but not positive images, as follows from evidence suggesting that hemispheric interaction benefits the performance of complex tasks, but not simple ones (Banich & Belger, 1990;Belger & Banich, 1992Compton, 2002;Compton et al, 2004;Koivisto, 2000;Passarotti et al, 2002;Pollman et al, 2003;Tremblay et al, 2009). Laterality is predicted to favor the RH for negative images and the LH for positive images, as follows from assumptions of the valence hypothesis (Ehrlichman, 1987;Silberman & Weingartner, 1986).…”
Section: Methodsmentioning
confidence: 86%
See 2 more Smart Citations